May footwear be a predisposing factor for the development of hallux rigidus? A review of recent findings - Colò, Gabriele; Fusini, Federico; Zoccola, Kristijan; Rava, Alessandro; Samaila, Elena Manuela; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2021)
Hallux rigidus (HR) is the clinical manifestation of osteoarthritis of the first metatarsophalangeal (MTP1) joint and affects about 2.5% of people older than 50 years. The condition may significantly impact patients' quality of life, leading to debilitating pain and limited range of motion (ROM). Numerous hypotheses have been postulated about contributing factors to the development of the disease, but with poor proven association. Some types of footwear over others may transmit altered pressure and stress toward the forefoot and this can significantly contribute to development of the condition. The purpose of this review is therefore to analyze the importance of correct footwear and if an incorrect shoe can influence the development and/or worsening of symptoms in patients affected by HR. From the results of the studies, it appears that symptoms improve with rigid-soled low-heeled shoes such as boots and worsen with flat flexible-soled shoes such as sandals and tennis shoes, which should therefore be avoided. Despite this, although incorrect footwear increases symptoms, a direct correlation with the development of the condition has not been detected but rather an improvement in comfort in some types of shoes than in others. In predisposed patients, incorrect footwear is more a way to increase symptoms than a real risk factor for the development of the disease, remaining in a very low risk percentage to be considered indicative.